Avanços e desafios nas políticas de promoção de acesso e permanência de estudantes negros (cotistas) na UFSCar - Barbosa, Maria Carolina Rosa Orlando (2022)
The black population represents more than half of the Brazilian population, however, social and economic indicators related to ethnic-racial groups in society are still unequal. The affirmative action policies adopted as a strategy to reduce inequalities in education have given special attention to higher education, due to the inequalities in the participation of white and black students at this level of education. These policies have achieved significant results expressed by the expansion in the numbers of black students in federal universities, but it is necessary to increase the policies that make possible the material and symbolic permanence of students at the university, allowing them to successfully reach the end of their academic career. This academic work seeks to analyze and discuss the problems and challenges related to the access and permanence of black students in public universities, focusing on the situation in the Federal University of São Carlos-UFSCar. The investigation was carried out based on bibliographic, documentary and field research. The field research was carried out with students who entered UFSCar through the system of vacancy reservation, in the ethnic racial criterion and associated income, that is, self-declared black, brown or indigenous students, who have completed high school in public schools, in addition to those entering the reservations for the disabled in the same group. The data collected at UFSCar contributed to the understanding of data regarding student trajectory and performance in the different types of admission to UFSCar from 2008 to 2022. The percentage of admission through vacancy reservation with the criterion of public school, went from 22 % in 2008, to 44% in 2022, despite the percentage having doubled in these 15 years, it is still lower than the number of students who entered through universal access in 2022, 56%. This evolution demonstrates the need to maintain and expand the measures that democratize access to universities, in addition to showing the importance of institutionalizing programs to support the permanence of students entering the vacancy reservation system. The analysis of the data collected in the field research shows that 60% of the students who answered the questionnaire remain at the university with their own resources, either through the help of family members or work, while the rest receive assistance from the university. The main difficulties presented by students are subsistence and those related to prejudice, discrimination, racism, feelings of helplessness and non-belonging. These questions point to the need and importance of advancing in institutional measures and programs that aim not only to expand access, but also to aim at the material and symbolic permanence of black students.